URDU 5 ISLAMIC PHILOSOPHY OF ECONOMICS IN THE EYES OF LATE DR. MAHMOUD AHMAD GHAZI: معاشیات کا اسلامی فلسفہ ڈاکٹر محمود احمد غازی ؒ کی نظر میں - siddiqui, munib; Arijo, Zain- ul-Abdin; Fatima, Sadaf (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2021)
It is a well-established fact that the times are moving, evolving and life is influenced by changes and developments and needs new issues and demands, new questions and their satisfying answers. On the other hand, Islam is the last religion of God Almighty. It is the only religion that fulfills the needs of all times, opposes changes and revolutions, and guides not only the Muslim Ummah but also the human race. Two centuries ago, society gave birth to many modern problems that continued to grow and reach their peak at a young age. The need for a leader has arisen, the need and importance of divine teachings and the usefulness and effectiveness of divine revelation have once again begun to attract the human race. There is a need to explore these modern issues that are growing up in the society in the light of lazy celestial sciences and to solve the complexities of this field, which is a contentious issue, which can be solved by a person, who spent his life in constant study and teaching, which is not only available in the higher sciences, but also in the second sciences. Now, where will such a person come from in this tempting age? The personality of the late Dr. Mahmood Ahmad Ghazi holds a prominent place in this category, who sheds light on Islamic teachings in every sphere of life, from beliefs, worship to political and cultural concepts, and then to modern economics and commerce. Understanding the requirements of modern times and solving the complexities of science well. When we talk about economy and trade, Dr. Sahib's speeches and writings often show the color of the intellectual movement of Hazrat Shah Waliullah Muhaddith Dahlavi and Imam Ghazali. The activities of economics are related to the worldly life of man, and there is no doubt that man cannot be free from affiliation with this field, because man is not just the name of the soul, but the soul with the body. It is said that the body needs many things. In the context of Islam, the discussion on economic activities can be divided into two parts. The status of worldly struggle is to succeed in the Hereafter, which is the real goal. Therefore, when it comes to economic activities, they will be as good as they will be in achieving the real goal. The second part deals with the legitimacy and non-legitimacy of the issues that have to be dealt with in daily life, whether the works are out of scope and what can be done with the protection of boundaries. This article will examine the reality of modern economics and the Islamic system of finance and economy in the light of Dr. Mahmood Ghazi's scholarly and intellectual tendencies and speeches, and will try to find an answer to the question that Dr. Ghazi's scientific and research endeavors. To what extent can it be a beacon for the next generation? And what links can future researchers make to solve the complexities?